EFEKTIVITAS MODEL PEMBELAJARAN MATEMATIKA REALISTIK BERBASIS BUDAYA BATAK TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA VIII SMP - Lubis, Ulfa Annisa; Lubis, Atipah; Rafidah, Rafidah; Tumanggor, Siti Halimah; Aurellia, Clarine; Tanjung, Fina Melini Panduwinata (FKIP Universitas Al Washliyah Medan, 2025)
The research was aimed at examining the extent to which the Realistic Mathematics Learning (RME) model rooted in local Batak cultural knowledge was able to improve students' understanding of mathematical concepts. A total of twenty eighth-grade students from Istiqlal Deli Tua Private Junior High School participated in this research which used a quantitative approach with a pre-experimental design of one group pretest-posttest. The research instrument was a geometry concept test in the context of Batak culture. Data were analyzed using the Paired Sample T-Test, N-Gain analysis, and homogeneity and normality tests. The results showed a significant increase in students' understanding of mathematical concepts, with an average score of 57.25 in the pretest to 86 in the posttest. The Paired Sample T-Test showed a statistically significant difference between before and after the application of the learning model with a significance value of 0.000 (<0.05). The average N-Gain score of 0.6940 placed the majority of students (60%) in the moderate improvement category, while the other 40% experienced a high increase. Thus, the Batak culture-based realistic mathematics learning approach has proven effective in deepening students' understanding of mathematical concepts. Research recommends utilizing local cultural knowledge as a learning resource to provide more relevant and meaningful mathematics learning for students.